Reklamlandskap - Holmberg, Kerstin (2007)
Outdoor advertising is not very often discussed within city planning even though the commercial messages occupy much of public space. The advertising signs affects not only the physical environment but also social life. In this report I would like to acknowledge and question the presence of advertising in our everyday environment.